Hubungan Bimbingan Belajar Orang Tua dan Konsep Diri Terhadap Hasil Belajar Matematika Siswa Kelas V SDN 4 Sesean - Yohanis Padallingan (LPPM UKI Toraja, 2021)
The formulation of the problem in this study are 1) is there are role for parental tutoring and self-concept on mathematics learning outcomes, 2) is there a positive ang significant relationship between parental tutoring and self-concept on student mathematics learning out comes? This research is a quantitative study and the design of this study uses pearsosn correlation analysis. Data collection using questionnaires, documentation and interviews. The subjects if this study were student of class Vb SDN 4 Sesean with a total population of students .sampling technique using the entire population as members of the sample. This instruments used to collect data in this study were a documentation questionnaire test and an interview. Data analysis using inferential statistics, namely simple correlation and multiple correlation, were analyzed using the SPSS 16.0 For Windows application for descriptive statistics and inferential statistics. Descriptive statistics are used to describe the variables in the from of average score, maximum score, minimum score, and standard deviation, while inferential statistics are used to test the hypothesis. The result of the study : 1) there is a positive and significant relationship with parental tutoring and mathematics learning outcomes with r count of 0,035. 2) there is a positive and significant relationship with self-concept and mathematics learning outcomes with r count of 0,035. The conclusion of this research is that there is a positive and significant significance of tutoring and self-concept towards the mathematics learning outcomes of the fifth grade students of SDN 4 Sesean.